THE INFLUENCE OF CAUSAL FACTORS OF PURCHASING INTENTION A USED CAR VIA FACEBOOK FANPAGE OF CONSUMERS IN BANGKOK AND ITS VICINITY - Pankham, Sumaman; Traisab, Kajon (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were to 1) develop and validate the consistency of causal of relationship modal of purchasing intention a used car and 2) study the influence of causal factors of purchasing intention a used car via Facebook Fan page of consumers in Bangkok and Its Vicinity. This research, quantitative research. Use the online questionnaire to collect the information. The sample group was who has been bought used car via Facebook Fan page Tee Rod Suay Meu Song and lived in Bangkok and Its Vicinity consisted of 480 people who were selected through quota sampling technique. Data were analyzed by using descriptive statistics to find the frequency and percentage. Inference statistics for relationship analysis used structural equations with a package program. The results of the research showed that a causal relationship modal of purchasing intention a used car via Facebook Fan page of consumers in Bangkok and Its Vicinity consisting 4 Variables were 1) Perceived Risk 2) Perceived Value 3) Consumer Attitudes and 4) Purchase Intention and the causal relationship model was developed in accordance with empirical data. Considering the value CMIN/df = 1.17, GFI = 0.97, AGFI = 0.95, CFI = 0.99, SRMR = 0.03 and RMSEA = 0.02. Coefficient of prediction = 0.83. This means that 83% of the variance in the model can explain the variation in the purchase intention of a used car through the Facebook Fan Page. The causal factors showed that Consumer Attitudes the most direct effect influence on Purchasing Intention a used car via Facebook Fan Page and Perceived Risk the most indirect effect influence on Purchasing Intention a used car via Facebook Fan Page.